Board Gender Diversity and Financial Stability: The Moderating Effect of Board Independence - Godwin Ahiase; N Nugraha; Maya Sari; Denny Andriana; Percy Chris Kpodo; Philipina Ampomah (Jurnal ASET (Akuntansi Riset), 2024)
This study examines the effect of board independence on the relationship between board gender diversity and financial stability in emerging African countries. A causal research design is employed, using data from 190 listed firms in nine emerging African economies covering 2012 to 2022. The study utilizes the two-step dynamic generalized moment method for data analysis. The findings reveal a significant relationship between board independence, financial stability, and gender diversity. The study underscores the importance of having a gender-inclusive board composition to enhance the resilience of companies operating in Africa. It also emphasizes the significance of board independence and effective board operations in promoting financial stability. The theory and practical implications are provided for policymakers and firm managers to enhance the financial stability of firms in emerging African economies. The study examines the combined relationship between board independence and gender diversity, highlighting the benefits of fostering independent and inclusive governance structures. The study contributes to academic discourse and establishes a strategic plan to foster sustainable development and stability in the corporate sector of emerging economies.